A Case Study to Evaluate the Introduction of Code Review in a Industrial Project - Guedes, Arthur Silva Lima; Alves, Everton L G (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2023)
A software development team often follows a set of phases to ensure the product achieves its objectives. During these phases, it is essential to adopt good practices, such as code review, to ensure code quality. This paper reports a case study that aimed to evaluate the impact of the adoption of code review on a software project developed by an agile team at the Hospital Israelita Albert Einstein. We analyzed quantitative and qualitative metrics to compare two stages of the project: before and after the introduction of code review. After the introduction of such practices, we observed a trend of bug reduction and improvements regarding code quality. The discussions between authors and reviewers also improved. Additionally, the project team found the changes made in the project very positive.